Training of School's Mailing Administration Based on Digital in “PAUD Mutiara Kids”, Traji Village, Temanggung District - Hengky Pramusinto; Ismiyati Ismiyati; Nita Dwi Yulianti (Universitas Negeri Semarang, 2023)
This community service aims to increase the knowledge and skills of Administration employees at Paud Mutiara Kids in managing incoming and outgoing letters to help smooth school activities. The method of implementing activities is planned using a participatory approach, with service work procedures that include training preparation, training implementation, training monitoring and evaluation, mentoring and mentoring monitoring and evaluation. The target of this community service is PAUD KIDS in Traji Village, Temanggung Regency. The results of this service activity, which was carried out on Tuesday, 24 August 2021, at Mutiara Kids Early Childhood Education, Traji Village, Temanggung Regency face-to-face as well as online, material delivery was carried out online via Zoom with a discussion of letter management at work while mentoring was carried out face-to-face with keep following health protocols by using e-agenda software. This activity concludes that the